South China Sea diplomacy : more needs to be done - Zha, Daojiong (2012)
Ongoing high-level diplomacy between China and the Philippines as well as Vietnam points to de-escalating tension over the South China Sea. A change of assessment in Beijing and Washington of each other in the region is a contributing factor. More diplomatic engagements between China and other claimant states are desirable.